Bills of Quantities: Perspectives of Contractor in Malaysia - Adnan, H.; Nawawi, A.H.; Akhir, S.M.; Supardi, A.; Chong, Heap Yih (INSInet Publications, 2011)
Bill of Quantities (BQ) have been used in Malaysia since their introduction to the industry by the British Colonial Government circa 1930. Many previous studies have carried out for the effectiveness of BQ, but very few discuss about the relationship between the usefulness of information in BQ at tendering stage and post - tendering stage from the view of the contractor. Therefore, this research would address the gap and analyse the usefulness of BQ to the contractor at the tendering and post - tender stage. Questionnaires were distributed to the contractors to obtain opinions regarding the BQ. It was found that although the BQ is useful to the Contractors at tendering and post-tender stage, the full potential is still not being achieved. Information in the BQ should be arranged in a directly useable way. It was found that, 'temporary work', 'work description' and 'prime cost-sum' are the key elements of the BQ information that need urgent improvement and presented in more meaningful format.